2021
DOI: 10.1111/jan.14753
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐existing mental health disorders in patients admitted to the intensive care unit: A systematic review and meta‐analysis of prevalence

Abstract: Aims To determine the reported prevalence rate of pre‐existing mental health disorders in patients admitted to adult ICUs and identify the most commonly occurring types of these disorders. Design Systematic review and meta‐analysis. Data sources Five electronic databases were searched from 1 January 2000 ‐15 April 2020. Google Scholar was used to perform forwards citation searching. Methods This review was conducted in line with the PRISMA guidelines and protocol registered with PROSPERO CRD42020181818. Meta‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…Our findings have potential implications for clinical practice, particularly for critically ill patients with pre-existing mental health disorders. A previous systematic review demonstrated that ~19% of adults in ICU suffer from such conditions, making them a significant subgroup [ 39 ]. Among the medications prescribed for mental health disorders, SSRIs are commonly used, including for depression, anxiety, and posttraumatic stress disorders [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have potential implications for clinical practice, particularly for critically ill patients with pre-existing mental health disorders. A previous systematic review demonstrated that ~19% of adults in ICU suffer from such conditions, making them a significant subgroup [ 39 ]. Among the medications prescribed for mental health disorders, SSRIs are commonly used, including for depression, anxiety, and posttraumatic stress disorders [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inequity in access to treatment and care contribute to overrepresentation of people with mental illness among people presenting with chronic and critical illnesses and an excess mortality (Pilowsky et al, 2021 ). Recognition of longstanding inequities and immense social and economic burden underpin calls internationally to improve healthcare for this population (Lawrence & Kisely, 2010 ; Mitchell et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of PMHDs on the long-term physical and mortality outcomes of ICU survivors is also well studied (12)(13)(14). However, the extent to which PMHDs exacerbate an episode of critical illness is poorly understood (15). The current study therefore aimed to determine the prevalence and types of PMHDs in patients admitted to an adult ICU using natural language processing (NLP) and investigated associations between the presence of a PMHD and ICU outcomes such as ICU length of stay and need for invasive ventilation.…”
mentioning
confidence: 99%